Bifunctional Graphene/γ‐Fe2O3 Hybrid Aerogels with Double Nanocrystalline Networks for Enzyme Immobilization. Issue 13 (19th February 2013) - Chen, Liang; Wei, Bin; Zhang, Xuetong; Li, Chun
Abstract: Highly porous hosting materials with conducting (favorable to electron transfer) and magnetic (favorable to product separation) bicontinuous networks should possess great potentials for immobilization of various enzymes in the field of biocatalytic engineering, but the synthesis of such materials is still a great challenge. Herein, bifunctional graphene/γ‐Fe2 O3 hybrid aerogels with quite low density (30–65 mg cm −3 ), large specific surface area (270–414 m 2 g −1 ), high electrical conductivity (0.5–5 × 10 −2 S m −1 ), and superior saturation magnetization (23–54 emu g −1 ) are fabricated. Single networks of either graphene aerogels or γ‐Fe2 O3 aerogels are obtained by etching of the hybrid aerogels with acid solution or calcining of the hybrid aerogels in air, indicative of the double networks of the as‐synthesized graphene/γ‐Fe2 O3 hybrid aerogels for the first time. The resulting bifunctional aerogels are used to immobilize β‐glucuronidase for biocatalytic transformation of glycyrrhizin into glycyrrhetinic acid monoglucuronide or glycyrrhetinic acid, with high biocatalytic activity and definite repeatability. Abstract : Graphene/γ‐Fe2 O3 hybrid aerogels with conducting (favorable to electron transfer) and magnetic (favorable to product separation) bicontinuous networks are fabricated for the first time and used to immobilize β‐glucuronidase for the biocatalytic transformation of glycyrrhizin into glycyrrhetinic acid monoglucuronide or glycyrrhetinic acid, with high biocatalytic activity and definite repeatability.